IMPLEMENTATION OF THE STEM APPROACH TO IMPROVING THE UNDERSTANDING OF CONCEPTS AND CREATIVITY OF JAMBI 4TH JAMBI CLASS VII STUDENTS ON ACIDS, BASES AND SALTS - Ratna Sari Dewi (International Jurnal of Education Schoolars, 2020)
To realize the Golden Generation of Indonesia and the challenges of a complex future, it is necessary to have a good and appropriate education pattern. Chemical materials integrated in science lessons at Madrasah Tsanawiyah (MTs) which are conceptual in nature make students more likely to memorize, for example; when students are faced with a natural event related to substances, they do not realize that the actual properties of acids, bases, and salts can be known naturally or artificially. The difficulty of students to understand substance materials in madrasah is also thought to be caused by the learning method used which focuses more on the completeness of the subject matter. The 2013 curriculum was designed by the government as a refinement of the previous curriculum (KTSP) which was deemed irrelevant to the demands of future generations. The development of this curriculum is designed using a scientific approach to improve higher-order, creative and critical thinking skills. One way to develop students' critical thinking skills in science learning is to develop the application of education with a STEM approach, students will be prepared to face the complex real world in order to be ready to face global competition. This is because Science, technology, engineering and mathematics are interrelated fields of science in human real life. These four fields must be mastered by students so that they can solve problems in the world of work, society, and in all aspects of life. In facing the era of global competition, Indonesia also needs to prepare reliable human resources in the STEM disciplines in quality and quantity.